Estimation of Population Dynamics Parameters of Selar crumenophthalmus Landed at Gorontalo Tenda Fish Landing Base: Pendugaan Parameter Dinamika Populasi Ikan Selar crumenophthalmus yang Didaratkan di Pangkalan Pendaratan Ikan Tenda Gorontalo - Nuralim Pasisingi; Ogyn Sutanto Mokoagow; Faizal Kasim (Habitus Aquatica, 2024)
This research aimed to determine the age group, growth, mortality, and yield per recruitment (Y/R) of Selar crumenophthalmus landed at Gorontalo City Tenda Fish Landing Base. A total of 1020 samples were collected randomly from fishermen who landed their catches at Tenda Fish Landing Base. The results of research based on sampling carried out twice a week from March to May 2023 showed that there were three age groups of S. crumenophthalmus. The percentages for age groups I, II, and III were 39.90%, 55.30%, and 4.30%, respectively. The asymptote length of the fish L∞ = 269.4 mm, the growth rate of the fish K = 0.55 and the theoretical age of the fish t0 = -0.1616 years. The natural mortality M = 0.48 was smaller than fishing mortality F = 0.85, total mortality Z = 1.33 per year, and total exploitation rate E = 0.64 per year. The Y/R value was 0.106 grams/recruitment with an exploitation rate of 0.608 per year.